Protective Role of Kynurenine 3-Monooxygenase in Allograft Rejection and Tubular Injury in Kidney Transplantation - Lassiter, Randi; Merchen, Todd D.; Fang, Xuexiu; Wang, Youli (Frontiers in Immunology, 2021)
Renal tubular epithelial cells (TECs) are the primary targets of ischemia–reperfusion injury (IRI) and rejection by the recipient’s immune response in kidney transplantation (KTx). However, the molecular mechanism of rejection and IRI remains to be identified. Our previous study demonstrated that kynurenine 3-monooxygenase (KMO) and kynureninase were reduced in ischemia–reperfusion procedure and further decreased in rejection allografts among mismatched pig KTx. Herein, we reveal that TEC injury in acutely rejection allografts is associated with alterations of Bcl2 family proteins, reduction of tight junction protein 1 (TJP1), and TEC-specific KMO. Three cytokines, IFNγ, TNFα, and IL1β, reported in our previous investigation were identified as triggers of TEC injury by altering the expression of Bcl2, BID, and TJP1. Allograft rejection and TEC injury were always associated with a dramatic reduction of KMO. 3HK and 3HAA, as direct and downstream products of KMO, effectively protected TEC from injury via increasing expression of Bcl-xL and TJP1. Both 3HK and 3HAA further prevented allograft rejection by inhibiting T cell proliferation and up-regulating aryl hydrocarbon receptor expression. Pig KTx with the administration of DNA nanoparticles (DNP) that induce expression of indoleamine 2,3-dioxygenase (IDO) and KMO to increase 3HK/3HAA showed an improvement of allograft rejection as well as murine skin transplant in IDO knockout mice with the injection of 3HK indicated a dramatic reduction of allograft rejection. Taken together, our data provide strong evidence that reduction of KMO in the graft is a key mediator of allograft rejection and loss. KMO can effectively improve allograft outcome by attenuating allograft rejection and maintaining graft barrier function.